A New Marker of Echinocandin Activity in an In Vitro Pharmacokinetic/Pharmacodynamic Model Correlates with an Animal Model of Aspergillus fumigatus Infection - Meletiadis, Joseph (Antimicrob Agents Chemother, 2018)
The lack of a quantifiable marker for echinocandin activity hinders in vitro pharmacokinetic/pharmacodynamic (PK/PD) studies for Aspergillus spp. We developed an in vitro PK/PD model simulating the pharmacokinetics of anidulafungin and assessing its pharmacodynamics against Aspergillus fumigatus with a new, easily quantifiable, sensitive, and reproducible marker. Two clinical A. fumigatus isolates previously used in animals (AZN8196 and V52-35) with identical anidulafungin EUCAST (0.03 μg/ml) and CLSI (0.015 μg/ml) minimal effective concentrations (MEC) and one isolate (strain AFU79728) with an MEC of >16 μg/ml were tested in a two-compartment PK/PD dialysis/diffusion closed model containing a dialysis membrane (DM) tube inoculated with 10(3) CFU/ml. During anidulafungin exposure, two types of fungal forms were observed inside the DM tube: floating conidia that were quantified by cultures and aberrant mycelia that were quantified by the vertical height of the mycelia attached on the DM tube. No aberrant mycelia were found for the resistant isolate or in the drug-free controls. An in vitro exposure-effect relationship was similar to that found in animals using survival as an endpoint, with a free-drug area under the concentration-time curve from 0 to 24 h (fAUC(0–24)) associated with 50% of maximal activity of 2.21 (range, 1.81 to 2.71) mg · h/liter in vitro versus 2.62 (range, 1.88 to 3.65) mg · h/liter in vivo (P = 0.41). The hillslopes were also similar, with 1.96 versus 1.34 (P = 0.29). Analysis of each isolate separately showed increased antifungal susceptibility between AZN8196 and V52-35 (P < 0.001) even though they have the same CLSI and EUCAST MECs, but the strains have two 2-fold dilutions lower MICs using Etest and the XTT {2,3-bis (2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenylamino) carbonyl]-2H-tetrazolium hydroxide} method. Dose fractionation studies with all three echinocandins showed that their activities are best described by fAUC and not the maximum concentration of free drug (fC(max)). The new marker correlated with in vivo outcome and can be used for in vitro PK/PD studies exploring the pharmacodynamics of echinocandins against Aspergillus spp.